Compressive and bending behaviours of wood-based two-dimensional lattice truss core sandwich structures. (June 2015) - Jin, Mingmin; Hu, Yingcheng; Wang, Bing
Abstract: In an effort to optimal the structure of wood engineering materials, wood-based two-dimensional lattice truss core sandwich structures made of wood composites and birch dowels were manufactured using a simple slotting and adhesive bonding approach. The out-of-plane compressive and bending behaviours of sandwich structures made of different facesheet materials were investigated. Analytical models were employed in this study to predict the compressive collapse strength and Young's modulus of the sandwich structures. The theoretical predictions of the compressive Young's modulus are in good agreement with experimental results based on the elastic deformation of the dowels. The failure modes of the sandwich structures are represented by the shear failure of the dowels and facesheets under out-of-plane compressive loads. The out-of-plane compressive behaviours of the sandwich structures demonstrate a good energy absorption capability which is an important factor for the safety of wooden construction. The bending behaviours of the sandwich structures indicate that the debonding of nodes was fatal to the sandwich structures, and the bending properties of the sandwich structures were found to depend on the fracture toughness of the adhesive and the strength of the facesheet materials used in their construction.